Importancia del uso de tecnologías modernas para análisis de calidad del agua de riego para cultivos agrícolas. - Figueroa Villasagua, Maria Michel (2022)
Technology is a set of tools, technical resources or procedures that are used in a certain field or agronomic sector, in this case we refer to the analysis of water quality through its use in crops because the development it has depends on this. the plants. Technology must be increasingly involved in agriculture. In addition, an analysis of the quality of the irrigation water must be carried out to determine the certain nutrients that are very helpful for the correct development of the plant, at the same time that this analysis is carried out, it will give certain important information about the parameters that the plant own water contains. The quality of water for irrigation must always be evaluating the physical or chemical conditions, the use of poor quality water can cause problems and harm the soil of crops. Excellent quality water is when it does not harm crop production, it is always possible to meet all the requirements and have a good production in agricultural crops. This device that is mentioned the pH-meter, conductivity meter helps to measure the quality of irrigation water, it also serves to determine the salinity content found in the main crops such as rice, corn, soybeans. In addition, it was determined that, in rice, corn, soybean crops that are not tolerant or sensitive to the salinity found in the irrigation water, it does affect production performance.